Cryptocurrency Sebagai Instrumen Investasi: Analisis Behavioral Factor Melalui Pengambilan Keputusan dan Performa Investasi Pada Investor Cryptocurrency di Indonesia - Hakim, Fikri Rafif; Sardion, Sintong Christian; Imansyah, Sulthan Rasyad (Syntax Literate, 2025)
Introduction: Cryptocurrency is an alternative investment instrument that offers high returns and risks. However, cryptocurrency investors in Indonesia tend to ignore the behavioral factors that influence them when making decisions about cryptocurrency. Purpose: This study aims to further examine behavioral factors or behavioral biases such as heuristics and herding held by cryptocurrency investors in Indonesia that will influence decision-making and ultimately affect the performance of their chosen investments. Methodology: Researchers used quantitative methods and online questionnaires to collect data. Data were taken from cryptocurrency investors in Indonesia. Researchers used PLS-SEM to test the hypothesis. Results: The results of this study indicate that there is a significant influence of overconfidence and herding on investment decision-making and investment performance in the cryptocurrency market, but the gambler's fallacy variable only has a significant effect on investment performance. Therefore, the role of investment decision-making as a mediator occurs only for the overconfidence and herding variables. On the other hand, the relationship between the variables shows positive results and contrary to the hypothesis, due to the strong influence of positive sentiment and the dominant upward movement of cryptocurrency prices during the study.